Distributed sleep transistor network for power reduction. - Changbo Long (IEEE Transactions on VLSI systems)
Sleep transistors are effective to reduce leakage power during standby modes. The cluster-based design was proposed to save sleep transistor area by clustering gates to minimize the simultaneous switching current per cluster and inserting a sleep transistor per cluster. In this paper, we propose a novel distributed sleep transistor network (DSTN), and show that DSTN is intrinsically better than the cluster-based design in terms of the sleep transistor area and circuit performance. We reveal properties of optimal DSTN designs, and then develop an efficient algorithm for gate level DSTN synthesis. The algorithm obtains DSTN designs with up to 70.7% sleep transistor area reduction compared to cluster-based designs. Furthermore, we present custom layout designs to verify the area reduction by DSTN.